Analisis Alternatif Pemilihan Biaya Siklus Hidup pada Masa Pemeliharaan Ruas Jalan Janti – Prambanan Km 7+759-8+750 - Rayendra Rayendra (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2019)
The highway is one of the land transportation infrastructure that serves to connect one area to another for public activities such as economics and social activities. Safe, comfortable, and efficient roads are not avoided by the availability of a flat road and no significant road damage.This research to calculate the life cycle cost analysis of the road with the calculation of pavement thickness that has been done by Ramadhani (2017). The method used in this research is by study case method, by collecting data about Janti-Prambanan Road section KM 7 + 750-8 + 750 and analyzing life cycle cost by estimating road maintenance that will be done during the life of the plan.Based on the analysis that has been done, the cost of construction or initial cost that must be issued based on the thickness of pavement set by Ramadhani (2017) with the total thickness of paved layer 50 cm is Rp. 14,089,007,000. The cost of maintenance at Alternative1 is Rp. 2.565.778.485,91 and at Alternative2 is Rp. 2,555,861,411.86. The total cost of the road life cycle in Alternative 1 is Rp. 16.654.785.485,91 while at Alternative 2 of Rp. 16,644,868,411.86. Analysis of the lifecycle cost of the two alternatives found EUAC for Alternative 1 is Rp. 65,649.89, while for Alternative 2 is Rp. 65,610.80. So that can be said by advancing the rehabilitation at least save on maintenance costs.